PENGARUH SUHU TERHADAP KADAR VITAMIN C KOMBUCHA TEH HITAM, TEH HIJAU, DAN EARLGREY SELAMA MASA SIMPAN - Vika Ayu Devianti; Lailatus Sa'diyah (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Kombucha is a fermentation drink of tea and SCOBY. One of the nutritious content of kombucha tea is vitamin C. Vitamin C in kombucha is produced by breaking down glucose by Sacharomyces. The longer fermentation lasts, the more sugar used by Sacharomyces, and it causes the decreasing of vitamin C content. The aim of this study is to determine the optimum temperature in controlling vitamin C content during the storage period of post-fermentation kombucha tea (7 and 14 days) and to compare the most stable kombucha tea (black tea, green tea and earl gray tea) in producing vitamin C after heating treatment. Vitamin C in kombucha obtained by measuring it’s absorbance in UV-Vis spectrophotometer at 265nm wavelength. The absorbance value will be calculated as the percentage of vitamin C content. The percentage calculation done by calculating the linear regression equation. The results obtained indicates that the most optimum temperature for controlling vitamin C during the storage period is heating it in 65oC for 15 minutes. Vitamin C is best produced from kombucha which is derived from green tea, black tea and then earl gray tea (sequentially). It can be concluded that heating kombucha in 65oC and 70oC is able to control the vitamin C value in black, green, and earlgrey tea kombucha